Finite Element Simulation of Downhole Stresses in Deep Gas Wells Cements - Nabipour, Amin; Joodi, B.; Sarmadivaleh, Mohammad (SPE, 2010)
Deep gas reservoirs are going to play more important roles in meeting growing demand of natural gas throughout the world. Due to extreme conditions of downhole stresses, pressure and temperature that occur in deep gas wells, maintaining cement mechanical integrity and zonal isolation have become critical concerns of industry during drilling, completion, and production of such wells. Cement sheath is expected to provide a flawless annular seal between casing and formation along the wellbore. However; cement failure cases which are being reported regularly show that there is still need for understanding extreme downhole conditions and the behavior of cement sheath experiencing such an environment. Although Uniaxial Compressive Strength (UCS) of cement is commonly regarded as the most important mechanical property of cement, recent theoretical and experimental results show that other mechanical properties of cement can be even more determinative in its failure.In this study, Finite Element Method (FEM), a widely-used robust numerical tool, is used for simulation of the downhole environment by modeling temperature, pressures, stresses, downhole materials and their interactions. Using this approach magnitude, direction and type of induced stresses in casing, cement, and formation have been determined. Furthermore; a series of sensitivity analyses was performed to reveal the effects of variation of various parameters such as casing internal pressure, differential horizontal stress and casing eccentricity, on the induced stresses in the cement sheath.Radial, tangential and von Mises stress profiles in the deep gas wells cements were investigated. Furthermore, the effect of casing internal pressure, differential horizontal stress and casing eccentricity were studied in the model. Results show that deep gas wells’ cements experience extreme amounts of thermal and mechanical stresses and special consideration is required in cement selection.